2020
DOI: 10.1155/2020/2348064
|View full text |Cite
|
Sign up to set email alerts
|

Study on Behind Helmet Blunt Trauma Caused by High-Speed Bullet

Abstract: The mechanism of Behind Helmet Blunt Trauma (BHBT) caused by a high-speed bullet is difficult to understand. At present, there is still a lack of corresponding parameters and test methods to evaluate this damage effectively. The purpose of the current study is therefore to investigate the response of the human skull and brain tissue under the loading of a bullet impacting a bullet-proof helmet, with the effects of impact direction, impact speed, and impactor structure being considered. A human brain finite ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Higher peak values of various biomechanical parameters in the frontal orientation are attributed to the larger curvature, relatively smaller surface area, relatively smaller standoff distance between the interior of the helmet shell and the headform. This observation is consistent with the finding in the literature (Tan et al, 2012;Pasquali and Gaudenzi, 2017;Palta et al, 2018;Cai et al, 2020). Palta et al (2018) observed the orientation-dependent BFD response in a computational model of ACH mounted on the rigid headform.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Higher peak values of various biomechanical parameters in the frontal orientation are attributed to the larger curvature, relatively smaller surface area, relatively smaller standoff distance between the interior of the helmet shell and the headform. This observation is consistent with the finding in the literature (Tan et al, 2012;Pasquali and Gaudenzi, 2017;Palta et al, 2018;Cai et al, 2020). Palta et al (2018) observed the orientation-dependent BFD response in a computational model of ACH mounted on the rigid headform.…”
Section: Discussionsupporting
confidence: 92%
“…The findings reported in this work are consistent with the finding in the literature. The BFD values obtained for headforms I and II (Table 2 a, b; Figure 6) are consistent with BFD values obtained in various computational and experimental investigations (Li et al, 2015;Rodríguez-Millán et al, 2016;Miranda-Vicario et al, 2018;Palta et al, 2018;Cai et al, 2020). Rodríguez-Millán et al (2016), using experiments and computational modeling, studied the response of rigid headform with witness material (i.e., R.P.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…2 a. The brain pressures, skull responses and the brain skull relative displacements have been verified refer to the relevant literature 27 29 , the material properties of bones and brain tissue are shown in Tables 2 and 3 . It can be used to study the dynamic response of the brain under the impact of rifle bullets and conduct injury analysis.…”
Section: Methodsmentioning
confidence: 94%
“…However, it is not a trivial task to improve the protective performance of a combat helmet without losing the real purpose of using composite materials, which is a decrease in weight. Traditionally, combat helmets have to be subjected to ballistic standards such as STANAG 2920 [5] or NIJ 0106.01 [6] and, consequently, they are analyzed at high impact velocities for the different ammunition [7][8][9][10][11][12], also under blast loadings [13][14][15][16][17][18]. However, the military industry has not focused on analyzing the Appl.…”
Section: Introductionmentioning
confidence: 99%